Analisis Faktor- Faktor yang Memengaruhi Nilai Perusahaan di Sektor Properti dan Real Estate Terdaftar di Bursa Efek Indonesia pada Tahun 2014 - 2018 - Andy Andy; Suwinto Johan (Universitas Tarumanagara, 2020)
The main issues examined in this study are the effect of profitability, capital structure, and firm size on firm value. The type of research used is descriptive research. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange, amounting to 55 companies. The sampling technique was determined by purposive sampling so that 24 companies could be sampled. The data used in this study are secondary data. The dependent variable is firm value and the independent variable is profitability of capital structure, and firm size. The analytical model used is multiple linear regression analysis.From the results of hypothesis testing it is found that: First, profitability has a significant effect on firm value with a sig value of 0,000 <α = 0.05. Second, capital structure affects the value of the company with a sig value of 0.024 <α = 0.05. Third, the size of the company affects the value of the company with a sig value of 0.699> α = 0.05. Fourth, profitability, capital structure, and company size significantly influence the value of the company with sig 0,000 <α = 0.05.Based on the results of the study, researchers suggest to companies 1. In order to continue to increase profits so that profitability with increased profitability will affect the increase in firm value. 2. In order to be able to maintain its capital structure in order to be able to influence the value of the company. In addition the company must also maintain assets because with high assets will increase the value of ln total assets so that the size of the company will be high which will have a positive influence on the value of the company.